A High-Voltage-Gain Non-Isolated Dual-Input Single-Output Soft-Switching DC–DC Converter With Low-Voltage Stress - Ahmed Alanssari; Mohd Rodhi Sahid; Razman Ayop; Farag Elghabsi; Mohammad Al Takrouri; Abdulhakeem Dobi (IEEE Access)
Multiple input non-isolated dc-dc converters remain very popular in applications involving hybrid energy integration. This is due to their compact structure and low cost in comparison with their isolated topologies counterparts. This paper proposed a high voltage gain high efficiency, soft-switching dual-input single-output dc-dc converter with low voltage stress for hybrid energy integration. The proposed converter achieves soft-switching for all the power switches at turn-on instants alongside high voltage conversion ratio. The coupled inductor is designed to facilitate ZVS and achieve high voltage gain eliminating the need for additional auxiliary circuits. This reduces the converter cost, number of components count and enhances efficiency. Furthermore, the voltage across the power switch is clamped with the help of an active clamp network. This facilitates the use of switches with low drain-to-source resistance ( $R_{ds ~on}$ ) hence reducing conduction losses and increasing the efficiency. Similarly, the operating modes of the converter as well as comparison with other similar converters are presented. In addition, experimental results obtained for 250 W prototype are presented which converts an input of 24 V dc to a 250 V dc at the output terminal with 97.8% efficiency.